MANAJEMEN KRISIS MASALAH SENGKETA LAHAN (Studi Kasus Pada Divisi Protocolaire And Internal Communication PT Krakatau Steel (Persero) Cilegon dalam Kasus Sengketa Lahan Kubangsari antara PT Krakatau Steel (Persero) Cilegon dengan Pemerintah Kota Cilegon) - Liza Diniarizky Putri (Universitas Serang Raya, 2015)
This research is focused to know crisis management strategy at Internal Communication and Protocolaire division at PT Krakatau Steel (PT KS) Cilegon in handling a legal dispute case of Kubang Sari land between PT KS and Cilegon city government, to know the implementation program which are done by Internal Communication and Protocolaire division PT KS, and also to criticize the lackness of crisis management system conducted by Internal Communication and Protocolaire division PT KS. This research is qualitative research. The result of the research shows that the strategy which is used in handling the legal dispute crisis of Kubang Sari land uses social recoveryprogram, and law solution. Social recovery program is a short term program that are focused to solve crisis for public, government, Non Government Organization, mass media, and other stakeholders, to eliminate negative thoughts towards company, to acknowledge the problem that really happen, and to return back the companies image in society, through negotiation, compromize, and lobbying. Then, law solution program tent to handle crisis through law systems. From this research, it can be concluded that PT KS managemet crisis is well enough, but there are still many lackness in applying media relation, and PT KS’s public relation doesn’t have crisis plan in the form of manual book to solve sudden crisis. Keywords: Crisis, Crisis Management, Public Relations